2019
DOI: 10.3892/mmr.2019.9889
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome inactivation driven by miR‑223‑3p reduces tumor growth and increases anticancer immunity in breast cancer

Abstract: MicroRNA-233-3p (miR-223-3p) is considered an important cancer-associated marker. The NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome represents a novel potential target for the treatment of breast cancer. Therefore, it was hypothesized that miR-223-3p may affect tumor growth and immunosuppression in breast cancer by inhibiting the NLRP3 inflammasome. In the present study, an increased expression level of NLRP3 was detected in three breast cancer cell lines compared with normal mammary epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 35 publications
4
43
0
Order By: Relevance
“…MiR-223-3p mimics suppressed NLRP3 expression, leading to an increased apoptotic rate and reduced proliferative capacity and ASC, IL-1β, and IL-18 expression levels. Consistent with "in vitro" results, "in vivo" experiments demonstrated that miR-223-3p reduced tumor growth and increased survival rate in mice (76). Collectively, these data indicate that targeting the inflammasome/IL-1 pathway with a miR-223-3p-like molecule could suppress the growth of BC cells by inactivation of the NLRP3 inflammasome.…”
Section: Inflammasomes and Bcsupporting
confidence: 80%
See 1 more Smart Citation
“…MiR-223-3p mimics suppressed NLRP3 expression, leading to an increased apoptotic rate and reduced proliferative capacity and ASC, IL-1β, and IL-18 expression levels. Consistent with "in vitro" results, "in vivo" experiments demonstrated that miR-223-3p reduced tumor growth and increased survival rate in mice (76). Collectively, these data indicate that targeting the inflammasome/IL-1 pathway with a miR-223-3p-like molecule could suppress the growth of BC cells by inactivation of the NLRP3 inflammasome.…”
Section: Inflammasomes and Bcsupporting
confidence: 80%
“…Zhang and colleagues showed that microRNA-223-3p (miR-223-3p) had an inhibiting effect on the NLRP3 pathways (76). Previous studies had already considered that MiR-223-3p may be involved in the regulation of inflammatory response, immunosuppression, cell growth and angiogenesis in different cancer cells (77,78).…”
Section: Inflammasomes and Bcmentioning
confidence: 99%
“…NLRP3 inflammasome could represent a novel potential target for the treatment of breast cancer [ 56 ]. In a recent preclinical study, the pharmacological inhibition of NLRP3 through miRNA reduced the tumor growth and the immune-resistance in breast cancer-bearing mice through ASC/IL-1/IL-18 pathways; these data provide new clinical insights for breast cancer management [ 57 ]. Notably, NLRP3 is associated with myocardial injuries, atherosclerosis, and diabetes mellitus [ 57 ]; high glucose stimulates NLRP3 expression thorough inhibition of its ubiquitinization in human cells [ 57 ]; therefore, we can speculate that hyperglycemia could enhance cardiotoxicity and responsiveness to ipilimumab through the NLRP3 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in-depth molecular studies [ 129 131 ] concluded that noncoding molecules such as miRNA are able to inhibit the activity of inflammasomes. It was found that miRNA-223 molecule binds to the 3′-UTR of NLRP3 mRNA and suppresses its protein expression, therefore blocking the priming and the production of IL-1 β [ 132 ].…”
Section: Molecular Inflammatory Events During Cancer Development Amentioning
confidence: 99%